2017
DOI: 10.5144/0256-4947.2017.265
|View full text |Cite
|
Sign up to set email alerts
|

Eleven-year review of data on Pap smears in Saudi Arabia: We need more focus on glandular abnormalities!

Abstract: BACKGROUNDWe reviewed data from Saudi Arabia on epithelial cell abnormalities (ECA) detected by Pap smear after noticing a slight increase in the incidence of cervical glandular abnormalities in our regional laboratory in recent years.OBJECTIVEClarify data on adenocarcinoma (ADCA) on Pap smears in Saudi Arabia.DESIGNDescriptive, retrospective study.SETTINGSRegional laboratory, Riyadh.PATIENTS AND METHODSWe reviewed all Pap smears of adult females between 2006 and 2016 and compared our data with previously publ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…Endometrial dilation and curettage are performed under anesthesia; however, Pap smears are easily performed. Similar to previously reported results, we found that Pap smears were useful in detection of glandular lesions [25].…”
Section: Discussionsupporting
confidence: 92%
“…Endometrial dilation and curettage are performed under anesthesia; however, Pap smears are easily performed. Similar to previously reported results, we found that Pap smears were useful in detection of glandular lesions [25].…”
Section: Discussionsupporting
confidence: 92%
“…On the basis of this study and previous studies, we found that it is beneficial to develop a risk prediction model that includes all significant risk factors in order to help clinicians identify high risk patients for further investigations. In Saudi Arabia as well as most of the developed countries, the pap smear test remain the first and easiest tool for cervical cancer screening 14. In this study, we quantified the risk of cervical cancer in symptomatic Saudi Arabian women.…”
Section: Discussionmentioning
confidence: 99%
“…In Saudi Arabia, the practice is to use the pap smear as a routine after delivery or if abnormal discharges occurs 14. The inadequate performance of the pap test15 focused our attention on developing a risk assessment tool that could incorporate various information on demographics, symptoms, and clinical and laboratory findings.…”
mentioning
confidence: 99%
“…This finding concurs with the findings of Al-Kadri et al ., 2015 and Nasser et al ., 2017, where n = 19,650 and 19,759, respectively, highlighting the need for greater focus on glandular abnormalities. [ 15 , 16 ] As shown in [ Table 2 ], the prevalence of abnormal Pap smears in our study was 3.05% (conventional and LBC methods); in Saudi Arabia, the prevalence rate was 14.52% in a single study due to a high rate of ASCUS, which was within the range according to their ASC/SIL ratio. [ 17 ] For detailed statistical data, see Appendix 1 and 2 .…”
Section: Discussionmentioning
confidence: 55%